Risk of solid organ transplant rejection following vaccination with seasonal trivalent inactivated influenza vaccines in England: A self-controlled case-series. Issue 31 (30th June 2016) - Dos Santos, Gaël; Haguinet, François; Cohet, Catherine; Webb, Dave; Logie, John; Ferreira, Germano L.C.; Rosillon, Dominique; Shinde, Vivek
Highlights: We assessed the risk of SOT rejection after seasonal influenza vaccination. We applied a self-controlled case-series method in transplant recipients in England. The study period encompassed three consecutive influenza seasons. Seasonal inactivated influenza vaccine use appears to be safe in SOT recipients. The results support current vaccination recommendations for this risk group. Abstract: Background: Annual seasonal influenza vaccination is recommended for transplant recipients. No formal pharmacoepidemiology study has been published on the association between solid organ transplant (SOT) rejection and vaccination with seasonal trivalent inactivated influenza vaccines (TIIVs). Methods: The risk of SOT (liver, kidney, lung, heart or pancreas) rejection after TIIV vaccination was assessed using a self-controlled case-series method (NCT01715792 ). SOT recipients in England with transplant rejection were selected from the Clinical Practice Research Datalink and linked Hospital Episode Statistics inpatient data. The study period (September 2006 to August 2009) encompassed three consecutive influenza seasons. We calculated the relative incidence (RI) of SOT rejection between the 30- and 60-day post-vaccination risk periods and the control periods (any follow-up period excluding risk periods), using a Poisson regression model. Results: In seasons 2006/07, 2007/08, 2008/09 and pooled seasons, 132, 136, 168 and 375 subjects, respectively, experienced at least one transplant rejection; approximately half (45%–51%) of these subjects had received a TIIV. For season 2006/07, the RI of rejection of any organ, adjusted for time since transplantation, was 0.74 (95% CI: 0.24–2.28) and 0.58 (95% CI: 0.24–1.38) during the 30-day and 60-day risk periods, respectively. Corresponding RIs for season 2007/08 were 1.21 (95% CI: 0.55–2.64) and 1.31 (95% CI: 0.69–2.48); for season 2008/09, 0.99 (95% CI: 0.43–2.28) and 0.64 (95% CI: 0.31–1.33); and for pooled seasons 1.01 (95% CI: 0.58–1.76) and 0.88 (95% CI: 0.56–1.38). The results of a separate analysis of kidney rejections and analyses that took into account additional potential confounders were consistent with those of the main analyses, with 95% CIs including 1 and upper limits below 3. Conclusion: This study provides reassuring evidence of the safety profile of TIIVs in SOT recipients, thus supporting current recommendations to vaccinate this risk group annually.